2009
DOI: 10.1039/b816914d
|View full text |Cite
|
Sign up to set email alerts
|

The generation and trapping of enantiopure bromonium ions

Abstract: Enantiopure bromonium ions may be generated from enantiopure bromohydrins and derivatives, they can be trapped with an in situ nucleophile to give enantiomerically pure products.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 29 publications
1
34
0
Order By: Relevance
“…However, rate and stereochemical findings from multiple prior studies require the alternative concerted scenario. 5a,7b,9a,b,14 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, rate and stereochemical findings from multiple prior studies require the alternative concerted scenario. 5a,7b,9a,b,14 …”
Section: Resultsmentioning
confidence: 99%
“…Proposed in 1937 by Kimball, 24 and further developed by Fahey, 9a,b Olah, 9c–e and Brown, 9f it has remained the usual scheme due to its conceptual simplicity, structural appeal, and, importantly, its reinforcement by the extensive and elegant work probing stabilized halonium ions. The conditions, however, under which those bridged onium ions are generated and probed are quite different from those used in synthetically relevant additions, so the derived mechanistic insights cannot be generalized with confidence.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, recent studies, most notably by the Denmark laboratory, bode well for the invention of new catalytic enantioselective methods. Denmark and co-workers, [35] building on the careful mechanistic work of Brown and co-workers, [36] have shown that enantiopure bromonium ions [37] may undergo degenerate halogen-exchange reactions with olefins, [36a] racemizing the halonium ions at rates competitive with nucleophilic capture. As unreacted alkene is present until the end of a catalytic reaction, the relative rates of racemization and nucleophilic capture must be overcome to achieve a successful catalytic enantioselective bromination.…”
Section: Asymmetric Halogenation Of Olefinsmentioning
confidence: 99%
“…Braddock et al showed that enantiopure haliranium ions can be prepared and subsequently trapped, [14] but it is often assumed that under halocyclization conditions haliranium ions might racemize by means of alkene-to-alkene transfer. Braddock et al showed that enantiopure haliranium ions can be prepared and subsequently trapped, [14] but it is often assumed that under halocyclization conditions haliranium ions might racemize by means of alkene-to-alkene transfer.…”
Section: Introductionmentioning
confidence: 99%